Uracil as a Zn-Binding Bioisostere of the Allergic Benzenesulfonamide in the Design of Quinoline-Uracil Hybrids as Anticancer Carbonic Anhydrase Inhibitors - Samar A. El-Kalyoubi; Ehab S. Taher; Tarek S. Ibrahim; Mohammed Farrag El-Behairy; Amany M. M. Al-Mahmoudy (MDPI AG, 2022)
A series of quinoline-uracil hybrids (10a-l) has been rationalized and synthesized. The inhibitory activity against hCA isoforms I, II, IX, and XII was explored. Compounds 10a-l demonstrated powerful inhibitory activity against all tested hCA isoforms. Compound 10h displayed the best selectivity profile with good activity. Compound 10d displayed the best activity profile with minimal selectivity. Compound 10l emerged as the best congener considering both activity (IC50 = 140 and 190 nM for hCA IX and hCA XII, respectively) and selectivity (S.I. = 13.20 and 9.75 for II/IX, and II/XII, respectively). The most active hybrids were assayed for antiproliferative and pro-apoptotic activities against MCF-7 and A549. In silico studies, molecular docking, physicochemical parameters, and ADMET analysis were performed to explain the acquired CA inhibitory action of all hybrids. A study of the structure-activity relationship revealed that bulky substituents at uracil N-1 were unfavored for activity while substituted quinoline and thiouracil were effective for selectivity.